Faktor-Faktor Determinan Yang Mempengaruhi Tingkat Kemiskinan Di Indonesia Dengan Indeks Pembangunan Manusia Sebagai Variabel Intervening - Dedi Saputra; Maya Panorama (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Poverty is a classic problem that occurs throughout the world, including Indonesia. During the last 10 years, the poverty rate in Indonesia has fluctuated, many economic factors are able to influence the poverty rate such as the open unemployment rate, the growth of zakat funds, and the human development index. Fluctuating developments were also experienced by the variable open unemployment rate, the growth of zakat funds, and the human development index, especially with the covid-19 pandemic that occurred, making it interesting to see whether these three variables were able to influence the poverty rate in Indonesia. This study aims to determine how the effect of the open unemployment rate and the growth of zakat funds on the poverty rate in Indonesia for the 2012-2021 period by using the human development index number as an intervening variable. This research is a quantitative type of research using eviws 10 as a data analysis tool, while the population in this study is the annual report data from the Central Statistics Agency and the National Amil Zakat Agency from 2012-2021 with a sample of 40 data. By using multiple linear regression and Sobel test to determine the indirect effect of the variable open unemployment rate, and the growth of zakat funds on the poverty rate with the human development index as an intervening variable. The results of this study explain that the open unemployment rate has a negative and significant effect on the human development index with a coefficient of -0.01 with prob. 0.00, the growth of zakat funds has a positive and insignificant effect on the human development index with a coefficient of 0.00 with prob. O.75 means that it is not significant, the open unemployment rate has a positive and significant effect on the poverty level with a coefficient of 0.54 with prob. 0.02, , the growth of zakat funds has a positive and insignificant effect on the poverty level with a coefficient of 69.01 and prob. 0.37, the human development index does not mediate the effect of the open unemployment rate on the poverty level as seen from the results of the one and two tailed Sobel test above 0.05, the human development index (IPM) does not mediate the effect of the growth of zakat funds (PDZ) on the poverty level (TK) evidenced by the results of one tailed and two tailed Sobel test above 0.05.